The long run health consequences of rural-urban migration - Janna E. Johnson; Evan J. Taylor (Quantitative Economics, 2019)
Rural-urban migration is an integral part of the structural transformation as societies move from a traditional agricultural economy to a modern economy. This process has many potential consequences for migrants. Our study focuses on the lifetime health effects of the large mid-20th century migration out of rural U.S. Northern Great Plains states, primarily to urban locations in the West and Midwest. An analysis of marginal treatment effects (MTEs) shows that (a) migrants are positively selected, and (b) the causal impact of migration is decreased longevity. Our evidence suggests that elevated mortality among migrants is linked to increased smoking and alcohol consumption.
Keywords: C31; I12; R23; 330; Rural-urban migration; mortality; marginal treatment effects